Cholesterol Granuloma of Chest Wall – A very Rare Benign Tumour - Nine, SMA Zulker; Haider, Md Zulfiqur; Ahmed, Md Sohail; Ahmed, Niaz; Khan, Md Saiful Islam; Hossain, Mohammad Delwar; Khan, Nazmus Sakib; Mehar, Tahera; Hasan, Md Kamrul (Cardiovascular Journal, 2020)
Cholesterol granuloma is a rare benign tumour and is described as inflammatory granulation that occurs in response to the deposition of cholesterol crystals. It is found most commonly in the paranasal sinuses or temporal bones, but there are also rare reports of their occurrence in the peritoneum, parotid gland, lymph nodes, thyroglossal duct, kidney, liver, and spleen. Involvement of the ribs has rarely been described previously. We report a case of cholesterol granuloma involving chest wall in second intercostals space of a 74-year-old male who presented with a slowly growing lesion of the anterior aspect of right side of the chest. Cardiovasc. j. 2020; 12(2): 158-161